IMMU-13. EFFICACY OF CXCR6 BLOCKADE AS A POTENTIATOR OF ANTI-PD-1 THERAPY FOR THE TREATMENT OF GLIOBLASTOMA. (9th November 2020) - Pant, Ayush; Saleh, Laura; Patel, Kisha; Medikonda, Ravi; Lim, Michael
Abstract: Glioblastoma (GBM) is an aggressive primary tumor of the brain with a dismal prognosis for patients. Despite the standard of care treatment, median survival is 12–15 months. The blockade of inhibitory checkpoints such as PD-1 and CTLA-4 has become the mainstay immunotherapy to treat solid tumors but it lacks efficacy in treating GBM patients. Emergence of alternative checkpoints on T cells as a mechanism of acquired resistance is considered one of the major hurdles for the success of anti-PD-1 therapy in GBM. Using an orthotopic mouse model of GBM, we have seen that cytotoxic T cells infiltrating the tumor show a preponderance of the chemokine receptor CXCR6 on exhausted cells. Furthermore, ablating CXCR6 along with anti-PD-1 therapy greatly improved anti-tumor immune response. Whereas PBS treated and CXCR6 KO mice had no long-term survivors 40 days post-tumor implantation, 90% of anti-PD-1 treated CXCR6 KO mice were long-term survivors, compared with 12% among anti-PD-1 treated wildtype mice. This supports our hypothesis that blockade of CXCR6 licenses anti-PD-1 blockade by alleviating acquired resistance to anti-PD-1 therapy. We have observed CXCR6 expression on exhausted T cells of GBM patients, making it a promising target for dual therapy with anti-PD-1 in clinical trials.